THE IMPACT OF ONLINE EDUCATION OVER THE UNIVERSITY OF PETROSANI STUDENTS DURING THE 2020 -2021 YEARS - EDUARD EDELHAUSER (Annals of the University of Petrosani: Economics)
Education was probably one of the most affect system by the COVID-19 crisis, but also one that react very quickly. The author questions themselves if this response was also a beneficial one for the University of Petrosani students. The author has made a huge investigation amongst the university students, to measure the result of online education over the University of Petrosani students after one year of online education. The survey was applied for 551 of the students from the Science and Mining Faculties, representing 26% of the whole students. The results are relevant and could influence the future development of this university in the next decade.